2020
DOI: 10.4103/japtr.japtr_28_20
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperlipidemic effects of apple peel extract in high-fat diet-induced hyperlipidemic rats

Abstract: Hyperlipidemia is generally managed with statin-based drugs. Simvastatin serves as a 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGR) inhibitor, with prolonged use proven to cause side effects. In the present study, antihyperlipidemic material is tested for its effect in lowering lipid in animals and its proven ability to bind to HMGR. Hyperlipidemia rats were divided into four groups, with different doses of 0, 57, and 114 mg/kg BW of apple peel extract (APE) and simvastatin (3.6 mg/kg BW). The total ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
2
4
0
1
Order By: Relevance
“…The more desired changes were observed in both: high-choline fed and high-fructose fed mice as apple peel supplementation led to HDL increase and TC, TG and LDL decrease [ 12 , 57 ]. Similar observations were made in hyperlipidemic rats, as apple peel supplementation significantly reduced serum LDL and increased HDL levels [ 58 ] and in diabetic rats, where a decrease in TC, LDL and TG with significant HDL elevation was observed [ 59 ]. This relationship was also present in tilapia, as apple peel powder supplementation reduced TC and TG levels in both the serum and liver [ 60 ].…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The more desired changes were observed in both: high-choline fed and high-fructose fed mice as apple peel supplementation led to HDL increase and TC, TG and LDL decrease [ 12 , 57 ]. Similar observations were made in hyperlipidemic rats, as apple peel supplementation significantly reduced serum LDL and increased HDL levels [ 58 ] and in diabetic rats, where a decrease in TC, LDL and TG with significant HDL elevation was observed [ 59 ]. This relationship was also present in tilapia, as apple peel powder supplementation reduced TC and TG levels in both the serum and liver [ 60 ].…”
Section: Resultssupporting
confidence: 70%
“…These differences might be caused by the variances in applied phenolic doses. It was calculated that human participants consumed approximately 306 mg/day of total phenolic compounds, while there were relatively higher doses used in the presented animal model studies, i.e., from 114 mg/kg to 1 g/kg [ 58 , 59 ]. The presented human study was also based on the small inhomogeneous metabolically group, so more studies in selected larger human groups could clarify this issue.…”
Section: Resultsmentioning
confidence: 99%
“…showed that oxidized LDL (oxLDL) promotes platelet aggregations through reduction of platelet NO; in turn, the activated platelets activate the uptake of oxLDL by macrophages. [ 24 ] This interaction leads to significant changes in the platelet indices as shown in the current study. Different studies have been shown that dyslipidemia may affect the metabolic activity of platelets, as oxLDL activates while HDL inhibits the atherogenic activity of platelets.…”
Section: Discussionsupporting
confidence: 58%
“…Quercetin, hyperoside, rutin and chlorogenic acid from hawthorn have been reported to inhibit HMGCR activity, and there are synergistic effects between the monomers after the combination [ 70 ]. Furthermore, Susilowati et al demonstrated that quercetin, chlorogenic acid, epicatechin and catechin from apple peel have inhibitory effects on HMGCR targets by molecular docking tests and in vitro experiments, leading to a combined inhibition of cholesterol synthesis [ 135 ].…”
Section: The Synergistic Hypolipidemic Mechanismsmentioning
confidence: 99%